Application of the Smart Cities concept in the City of Recife-PE (Research, Society and Development, 2021)
Technological advances are now part of the routines of cities, which make it possible to offer services focused on improving the lives of the population that lives there. For a given city to be recognized as a Smart City, it is essential to fulfill specific requirements called indicators. Therefore, this article aims to identify evidence of the application of smart city concepts in Recife. As for the methodology, it is a qualitative approach, of the exploratory type, where the data collection technique will be the literature review, from secondary sources, using content analysis to study the information obtained. In this sense, it appears that the Municipal Human Development Index - IDHM is a widely used tool to stimulate the measurement, discussion, and conceptualization of "development" in the broadest way, through national socioeconomic indicators, considering topics such as health, education, income, work, housing and vulnerability. Therefore, using the IDHM as a reference, it is possible to affirm that the State of Pernambuco occupies the 17th position in the national ranking, and in turn, Recife occupies the 53rd position among all Pernambuco municipalities, with the IDHM of 0.772.